2010
DOI: 10.1200/jco.2009.25.8376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Neoadjuvant Chemoradiotherapy Regimens for Locally Advanced Rectal Cancer: Results of the Phase III Trial ACCORD 12/0405-Prodige 2

Abstract: The benefit of oxaliplatin was not demonstrated and this drug should not be used with concurrent irradiation. Cap 50 merits investigation for T3-4 rectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
369
8
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(426 citation statements)
references
References 22 publications
28
369
8
21
Order By: Relevance
“…At the moment, a final conclusion cannot be drawn until the definitive results of the ongoing CAO/AIO/ARO-04 trial are available. However, results similar to those in the present study were reported by Gérard et al [12] after analyzing the results of the ACCORD 12/0405-Prodige 2 trial. In this study, additional oxaliplatin was not found to be more effective than 5-FU alone for preoperative RCT in rectal cancer patients.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…At the moment, a final conclusion cannot be drawn until the definitive results of the ongoing CAO/AIO/ARO-04 trial are available. However, results similar to those in the present study were reported by Gérard et al [12] after analyzing the results of the ACCORD 12/0405-Prodige 2 trial. In this study, additional oxaliplatin was not found to be more effective than 5-FU alone for preoperative RCT in rectal cancer patients.…”
Section: Discussionsupporting
confidence: 54%
“…Proven indications exist for the use of intensified chemotherapy as a standard regimen for advanced stage local tumors and expanding tumor growth [12,14,39,40]. The use of an induction chemotherapy followed by standard RCT with 5-FU monotherapy might be more effective concerning tumor response without increasing acute toxicity during RCT [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of adding oxaliplatin into the neoadjuvant treatment is supported by the study ACCORD 12/405, which compared concomitant chemo-radiotherapy comprising capecitabine against to the same treatment supplemented with oxaliplatin. The results did not prove any signifi cant advantage of the combined chemotherapy and recommended capecitabine as "merits investigation" for T3 and T4 tumours (10). Attempts to increase the outcome of combined neoadjuvant chemo-radiotherapy have lead to numerous phase 2 studies with tumour targeted drugs.…”
Section: Discussionmentioning
confidence: 94%
“…В целом показатели токсичности были приемлемыми и соответ-ствовали данным крупных зарубежных рандомизиро-ванных исследований, где также использовали оксали-платин в сочетании с фторпиримидинами [14,15]. При сравнении межгрупповых показателей токсичности наи-более предпочтительным вариантом неоадъювантного лечения выглядит ЛТ на фоне приема капецитабина или оксалиплатина+капецитабина.…”
Section: Discussionunclassified